The impact of graded levels of fermented plant protein (Proteger®) in extruded foods on fecal quality, nutrient digestibility, and colonic fermentation in beagle dogs - Chen, Youhan; Aldrich, Charles Gregory (Frontiers in Animal Science, 2025)
IntroductionMicrobially fermented plant protein (FPP) has been demonstrated to have high protein digestibility and palatability for terrestrial animals although no work has previously been published describing this for pets. The objectives of this study were to evaluate the nutritional value of FPP, its performance in extrusion processing to produce pet food, and graded inclusion levels on diet utilization in dogs.MethodsFour experimental diets were produced on a single-screw extruder with processing data and samples collected at 15-min intervals. The control diet without FPP contained 15% soybean meal (SBM); soybean meal was replaced by FPP at 5%, 10%, and 15% to create three diets with graded levels of FPP (5FPP, 10FPP, and 15FPP). The experimental diets were fed to 12 adult dogs in a 4 × 4 replicated Latin square design. Dogs were given these diets for 9 days followed by a 5-day total fecal collection. Fresh fecal samples were collected for hindgut fermentation evaluation. Apparent total tract digestibility was calculated by total fecal collection and titanium dioxide marker methods. Data were analyzed using a generalized linear mixed model with diet as a fixed effect and dog and period as random effects. Least-square means were analyzed with a single degree of freedom contrasts at significance level of a = 0.05.ResultsThe preconditioner steam injection rate showed a linear decrease (P < 0.05) as FPP increased in dog diets. The sectional expansion index (SEI) was greater (P < 0.05) in kibbles with 5FPP and 15FPP compared to SBM. Food intake and dog fecal scores were not impacted by FPP inclusion. Dogs fed 15FPP had greater (P < 0.05) crude protein digestibility than those fed SBM, with no significant effects on fecal pH, ammonia, or short-chain fatty acid production. For palatability, dogs preferred SBM over 5FPP and 10FPP but did not show a difference between SBM and 15FPP.DiscussionOverall, including up to 15% FPP in extruded dog diets promoted kibble expansion without negatively affecting animal acceptability, fecal quality, nutrient digestibility, or hindgut fermentation.